Mengenal Budaya Batak Toba Melalui Falsafah “Dalihan Na Tolu” (Perspektif Kohesi dan Kerukunan) - Adison Adrian Sihombing (Jurnal Lektur Keagamaan, 2018)
Dalihan Natolu is understood as the identity and rules that govern the social system and as a determining factor in the custom of Batak culture. There are several studies about the meaning and values of this philosophy. This article intended to search and to find the philosophical foundation of Dalihan Natolu. At the same time, this article also wants to show how is “the das sollen” and “das sein” of Dalihan Natolu in the recent time. The method used in this research is qualitative descriptive-interpretative method in the perspective of philosophy of phenomenology and library research. The results of this research shows that Dalihan Natolu is the manifestation of the essence of life of the human being itself and the result of the search for the depth of the life of Batak Toba people. Dalihan Natolu is the manifestation of the nature of the Debata Natolu (Triune God). He becomes the pillar and guarantor of a harmonious life of the entire order of the Toba Batak culture in order to pursue and reach happiness of life (das sollen). Unfortunately, there have been shifting and deviations of values and also perspective changing about the position of the three functional groups in Dalihan Na Tolu itself called Hula-hula, Dongan Sabutuha, and Boru (das sein).Keywords: Dalihan Na Tolu, Hula-hula, Dongan Sabutuha, BoruDalihan Natolu dipahami sebagai identitas dan pedoman hidup yang mengatur sistem kekerabatan serta menjadi faktor penentu dalam adat budaya Batak. Tulisan ini memiliki dua tujuan yaitu: mencari dan menemukan landasan filosofis Dalihan Natolu; dan menampilkan bagaimana “das sollen” dan “das sein” Dalihan Natolu di zaman “now”. Metode penelitian yang digunakan adalah kualitatif deskriptif-interpretatif dalam perspektif filsafat fenomenologi dan penelitian kepustakaan. Hasil penelitian menunjukkan bahwa Dalihan Natolu merupakan perwujudan hakikat hidup manusia itu sendiri dan merupakan hasil pencarian makna hidup suku Batak Toba. Dalihan Natolu merupakan perwujudan dari hakikat Debata Natolu (Allah yang tiga). Dia menjadi tiang penyangga dan penjamin menuju kehidupan yang harmonis. Namun demikian telah terjadi pergeseran, penyimpangan nilai serta perubahan cara pandang akan posisi kedudukan ketiga golongan fungsional yang ada dalam Dalihan Natolu, yaitu Hula-hula, Dongan Sabutuha, dan Boru.Kata kunci: Dalihan Na Tolu, Hula-hula, Dongan Sabutuha, Boru